2016
DOI: 10.1111/hepr.12637
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of pathological vascular invasion in hepatocellular carcinoma within 3 cm and three nodules without radiological vascular invasion

Abstract: AFP of more than 100 ng/mL and PIVKA-II of more than 100 mAU/mL can predict pathological vascular invasion in patients with HCC within 3 cm and three nodules without radiological vascular invasion. In treating such cases, hepatic resection rather than local ablation therapy is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 39 publications
(45 reference statements)
3
15
0
Order By: Relevance
“…Yamashita et al demonstrated that not only the presence of microinvasion such as portal venous, hepatic vein, bile duct infiltration, but also the presence of intrahepatic metastasis (satellites) is the best indicator of a poor prognosis after HR and transplantation. Therefore, MI‐HCC may be considered an important entity (superior to the only presence of vascular microinfiltration) to determine the prognosis of patients submitted not only to HR or liver transplantation but also to ablation therapies . Our study showed that IOUS definition of MI‐HCC had a high agreement with the histological findings, such as the satellites detection and the correct measurement of HCC diameter (see Table ) and the type of IOUS examination (through either a laparoscopic or an open approach) did not influence these results (see Table ).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Yamashita et al demonstrated that not only the presence of microinvasion such as portal venous, hepatic vein, bile duct infiltration, but also the presence of intrahepatic metastasis (satellites) is the best indicator of a poor prognosis after HR and transplantation. Therefore, MI‐HCC may be considered an important entity (superior to the only presence of vascular microinfiltration) to determine the prognosis of patients submitted not only to HR or liver transplantation but also to ablation therapies . Our study showed that IOUS definition of MI‐HCC had a high agreement with the histological findings, such as the satellites detection and the correct measurement of HCC diameter (see Table ) and the type of IOUS examination (through either a laparoscopic or an open approach) did not influence these results (see Table ).…”
Section: Discussionsupporting
confidence: 49%
“…Therefore, MI-HCC may be considered an important entity (superior to the only presence of vascular microinfiltration) to determine the prognosis of patients submitted not only to HR or liver transplantation 4,7,36 but also to ablation therapies. [37][38][39] Our study showed that IOUS definition of MI-HCC had a high agreement with the histological findings, such as the satellites detection and the correct measurement of HCC diameter (see Table 3) and the type of IOUS examination (through either a laparoscopic or an open approach) did not influence these results (see Table 4). This analysis is also valid in the subgroup of patients with HCC diameter ≤2 cm (see Table 5).…”
Section: Discussionmentioning
confidence: 51%
“…Many reports have noted the heterogeneity of small HCC ≤3 cm, and some of these tumors display microvascular invasion (MVI) ranging from 18.1% to 37.0%, which indicated locally advanced HCC . We previously reported that HR with a wide margin (>0.5 cm) led to better survival in patients with solitary HCC ≤2 cm that displayed MVI.…”
Section: Introductionmentioning
confidence: 99%
“…32 If RFA was inadequately applied for such tumors, abnormal recurrence, such as intrahepatic dissemination, can occur. 34,35 Therefore, for those patients, we should avoid RFA regardless of the patients' functional reserve.…”
Section: Discussionmentioning
confidence: 99%